Delayed cortical development in mice with a neural specific deletion of β1 integrin - Rashid, Mamunur; Olson, Eric C. (Frontiers in Neuroscience, 2023)
The adhesion systems employed by migrating cortical neurons are not well understood. Genetic deletion studies of focal adhesion kinase (FAK) and paxillin in mice suggested that these classical focal adhesion molecules control the morphology and speed of cortical neuron migration, but whether β1 integrins also regulate migration morphology and speed is not known. We hypothesized that a β1 integrin adhesion complex is required for proper neuronal migration and for proper cortical development. To test this, we have specifically deleted β1 integrin from postmitotic migrating and differentiating neurons by crossing conditional β1 integrin floxed mice into the NEX-Cre transgenic line. Similar to our prior findings with conditional paxillin deficiency, we found that both homozygous and heterozygous deletion of β1 integrin causes transient mispositioning of cortical neurons in the developing cortex when analyzed pre- and perinatally. Paxillin and β1 integrin colocalize in the migrating neurons and deletion of paxillin in the migrating neuron causes an overall reduction of the β1 integrin immunofluorescence signal and reduction in the number of activated β1 integrin puncta in the migrating neurons. These findings suggest that these molecules may form a functional complex in migrating neurons. Similarly, there was an overall reduced number of paxillin+ puncta in the β1 integrin deficient neurons, despite the normal distribution of FAK and Cx26, a connexin required for cortical migration. The double knockout of paxillin and β1 integrin produces a cortical malpositioning phenotype similar to the paxillin or β1 integrin single knockouts, as would be expected if paxillin and β1 integrin function on a common pathway. Importantly, an isolation-induced pup vocalization test showed that β1 integrin mutants produced a significantly smaller number of calls compared to their littermate controls when analyzed at postnatal day 4 (P4) and revealed a several days trend in reduced vocalization development compared to controls. The current study establishes a role for β1 integrin in cortical development and suggests that β1 integrin deficiency leads to migration and neurodevelopmental delays.